Peran Perencana dalam Era Demokratisasi Perencanaan: Kasus Perencanaan Jalan Dago-Lembang - Elkana Catur Hardiansah (The Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
This paper aims at exploring the connection between rationality and power, also the role needed to be taken by planners in the era of democratization of planning. This study will use phonetic planning research approach. This will cover epicentrism analysis, technique and will involve judgment and decision made by political actors involved. The analysis conducted will include rationality of relation and power, political moves by the actors that led to the interpretation of planner's roles in the era of democratization of planning. A planner, not only a skill in field study but also multi-functional skill in any profession in must do the role as technician, bureaucrate, advocate and politician. Dimension for each role certainly have different definition according to the concept of the job.Keywords: participation, democratization planning, phonetic approach